Should patients undergo ascending aortic replacement with concomitant cardiac surgery? - Yalcin, Mihriban (Cardiovasc J Afr, 2016)
AIM: To determine whether concomitant surgery is a predictor of mortality in patients undergoing surgery for ascending aortic aneursym. METHODS: Ninety-nine patients who underwent ascending aortic aneursym surgery between January 2010 and January 2015 were included in this study. Nineteen patients underwent ascending aortic replacement (RAA) only, 36 underwent aortic valve replacement (AVR) and RAA, 25 underwent coronary artery bypass grafting (CABG) and RAA, 11 underwent the Bentall procedure, and eight underwent AVR, CABG and RAA. RESULTS: Depending on the concomitant surgery performed with RAA, the mortality risk increased 2.25-fold for AVR, 4.5-fold for CABG, 10.8-fold for AVR + CABG and four-fold for the Bentall procedure, compared with RAA alone. CONCLUSION: Concomitant cardiac surgery increased the mortality risk in patients undergoing RAA, but the difference was not statisticaly significant. Based on these study results, patients undergoing cardiac surgery, with a pre-operative ascending aortic diameter of over 45 mm, should undergo concomitant RAA.